Alexander Hammid - Moucha, Josef (Iluminace, 2000)
Review of Jaroslav Anděl's monograph Alexandr Hackenschmied.
Keywords: book review; American photographer and filmmaker of Czech origin; film literature; Alexandr Hackenschmied